A web-based collaboration approach for teaching in medicine - Alves, Victor (2006)
Teaching medicine requires developing a vast range of manual, intellectual, visual and tactile skills as well as taking into account large amounts of factual information. Traditional medical teaching and individual learning in particular, can be complemented with electronic web based systems. One of the main impacts of e-Teaching in education resides in the fact that it provides opportunities to create resources that turn the learning process flexible. This implies a different relation between teachers and students and even between institutions, in the sense that the students participate on their own formation and the vertical hierarchy tends to become increasingly more horizontal. Awareness of the knowledge constructing process is increased, and consequently more satisfaction gained from learning. In this paper we describe a webbased collaboration approach for teaching that is being developed to simulate conversational dialogue in the area of Medicine, that enables the integration of highly heterogeneous sources of information into a coherent knowledge base accessed from web-based interfaces, either from the tutor’s point of view or the development of the discipline in itself, i.e. the system’s content is created automatically by the physicians as their daily work goes on.